Web Based Public Complaint Service System - Mei Ismi Nuryati; Hidayatur Rakhmawati; Mita Aulia Maharani; Raihan Rizqi Rahmatulloh; Alun Suyufi; Yuyun Kurniasih (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This research is motivated by the suboptimal quality of public services and the management of public complaints, which are still conventional (manual recording, verbal, or text messages) in many villages in Indonesia, including the Purwodadi Village Hall. Based on observations, the Purwodadi Village Hall does not yet have an integrated system to accommodate, manage, and monitor complaints in a structured manner. This results in complaint data often not being optimally documented and difficult to use as evaluation material. Starting from these problems, this study aims to design and implement a Web-Based Public Complaint Service System at the Purwodadi Village Hall. The development of this system uses the Waterfall Method, which is part of the Software Development Life Cycle (SDLC), including the stages of needs analysis, system design, coding, testing, and maintenance.